1998
DOI: 10.1111/1540-5885.1520167
|View full text |Cite
|
Sign up to set email alerts
|

Commercializing Nascent Technology: The Case of Laser Diodes at Sony

Abstract: To develop really new products, a company often needs to get a handle on really new technologies. Although some breakthrough products simply combine existing technologies in novel ways, other innovations require the successful commercialization of nascent technologies. In other words, such innovations depend on entirely new structures and methods that have been demonstrated in a research environment but have not yet been refined to the point where they are ready for production. The path from nascent technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…While the first two were also positively influenced by external HR manufacturing capabilities, the latter two are negatively influenced by external HR manufacturing sources and a trade-off needs to be considered. In their examination of Sony's commercialization of laser diodes, Wood and Brown (1998) identified different managerial approaches that are supportive of a successful commercialization of nascent technologies. Among others, they found that a transfer of employees from the research department to the development team during the implementation stage facilitates technology commercialization.…”
Section: Antecedents and Success Factors Of Technology Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first two were also positively influenced by external HR manufacturing capabilities, the latter two are negatively influenced by external HR manufacturing sources and a trade-off needs to be considered. In their examination of Sony's commercialization of laser diodes, Wood and Brown (1998) identified different managerial approaches that are supportive of a successful commercialization of nascent technologies. Among others, they found that a transfer of employees from the research department to the development team during the implementation stage facilitates technology commercialization.…”
Section: Antecedents and Success Factors Of Technology Commercializationmentioning
confidence: 99%
“…Crossing organizational boundaries, personal contacts between the researchers in the companies and the researchers from universities are important for successful technology commercialization Thursby 2001, 2003). In the same manner, a strong and effective cooperation in the manufacturing stage, between engineers engaged in process development and those engaged in production is required (Wood and Brown 1998;Duhm and Wielockx 1991).…”
Section: Antecedents and Success Factors Of Technology Commercializationmentioning
confidence: 99%
“…These new fields must first be identified in what it is an exploratory and creative process, demanding different competencies, methods and information in comparison to the optimization of existing market segments (Wood;Brown, 1998;Lynn;Heintz, 1992;Hamel;Prahalad, 1991). The identification of possible application fields requires an examination of abstract functions where the emerging technology (or technology combination) can compete.…”
Section: Unknown Application Fieldsmentioning
confidence: 99%
“…Thus, depending on the timeline of the forecast, an analysis based on a constant slope may be more accurate at certain points than at others. Source: Wood and Brown 1998) …”
Section: Historical Experience Curvesmentioning
confidence: 99%